Understanding the perception concerning medication and types of adherence behaviour in hypertensive patients - Lee, Khuan; Mokhtar, Halimatun Halaliah; Krauss, Steven Eric; Ong, Beng Kok (Universiti Putra Malaysia Press, 2012)
Hypertension is a significant public health problem. Despite the availability of effective treatment, non-adherence to treatment has been identified as the main cause of failure in controlling hypertension. The fragmented pattern of research related to adherence is unavoidable because it is a complex phenomenon and affects not only the health of patients but also their entire lives. The research gap in this field is the absence of the patients’ perspective and a dearth of qualitative research. The aim of this study was to understand the patients’ perception concerning medication and the extent that these perceptions are reflected in adherence behaviour. This is a qualitative exploratory study on hypertensive patients in a community health clinic in the state of Selangor, Malaysia. It was found that the participants perceive prescribed Western Medicine (WM) from the clinic as scientifically proven but has undesirable side effects. Therefore, Complementary and Alternative Medicine (CAM) are used to counteract the harmful effects of WM. The types of adherence behaviour found include faithful follower, self-regulator and intentional non-adherer. The reason to engage in particular adherence behaviour indicates a contextual relationship with the perception concerning the medication. Thus, it was concluded that patients acquire knowledge phenomenologically to cope with hypertension. Therefore, to improve self-management and self-efficacy in adherence with treatment, patient-tailored education and an empowerment approach should be introduced.